THE ROLE OF LOCAL TAXES IN THE FORMATION OF REVENUES OF LOCAL BUDGETS - HRYTSENKO , Olga (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The system of financial support of the social process of the country must constantly adapt to the influences of the external environment both in the conditions of the hybrid war with Russia and in the conditions of the post-war period. This requires systemic transformational changes in the socio-economic environment, reform of the financial system, further improvement of the decentralization of the management of state financial resources, since expenditures from the state budget to cover the costs of armaments and ensuring the independence of Ukraine will have a large specific weight annually. Under such conditions, local budgets will rely more and more every day on the tasks of financing a significant part of the social needs of the local population. Accordingly, the effectiveness of regional systems of taxation of individual territories with local taxes and fees is primarily confirmed by volumes sufficient to form the revenue part of local budgets for the purposes of ensuring the successful functioning of territories of local importance and their development. Therefore, the role of local taxes and fees is growing daily and contributes to the accumulation of the amount of financial resources necessary for the development of both territorial communities and the state as a whole, which will significantly reduce the burden on the state budget of the country. The article examines problematic aspects of the formation of revenues and expenditures of local budgets in difficult economic conditions arising under the influence of a hybrid war with Russia. Emphasis is placed on the necessity of restructuring the national budget policy in the context of the formation of guarantees for the financial support of the social needs of the population of Ukraine, its comprehensive protection and the creation of decent working and living conditions. The important role of local taxes in the formation of revenues of local budgets of territorial communities is substantiated based on the systematization of the approaches of scientists and the conducted expert assessment of the state and changes of local budgets in 2021-2022. Problematic aspects in the payment of local taxes are identified and the ways to solve them are outlined. The need for further improvement of the tax legislation, capable of ensuring the formation of a new tax model for the purposes of optimizing the tax regulation of payment of local taxes and increasing revenues to the local budget, has been proved.
Keywords: local taxes; local budget; tax regulation; optimization of payment of local taxes